Tracking triggering mechanisms for soft-sediment deformation structures in the Late Cretaceous Uberaba Formation, Bauru Basin, Brazil - Alessandretti, Luciano; Warren, Lucas Verissimo [UNESP]; Martinho dos Santos, Mauricio Guerreiro; Virga, Matheus Carvalho (Soc Brasileira Geologia, 2020)
Soft-sediment deformation (SSD) structures are widespread in the sedimentary record, and numerous triggering mechanisms can induce its development, including glaciation, earthquakes, overloading, ground-water fluctuations, and wave movement. The Late Cretaceous Uberaba Formation preserves SSD structures as small- and large-scale load casts and associated flame structures, pseudonodules, and convolute laminations observed in the contact of three well-defined intervals among fine- to coarse-grained lithic and conglomeratic sandstone with fine-grained arkose and mudstone beds. Based on the morphology of the SSD structures, sedimentary facies of the Uberaba Formation, and similarities with previous observations in the geological record and laboratory models, these features are assigned to liquefaction-fluidization processes as the major deformational mechanism triggered by seismic and aseismic agents. We propose that a deformation occurred just after the sedimentation triggered by seismic shock waves and overloading, induced by the sudden deposition of coarse-grained sandy debris on fine-grained sediments. Some of these structures can be classified as seismites, providing evidence of intraplate seismicity within the inner part of the South American Platform during the Late Cretaceous. This seismic activity is likely related to the uplift of the Alto Paranaiba High along reactivations of regional structures inherited from Proterozoic crustal discontinuities and coeval explosive magmatism of the Minas-Goias Alkaline Province.
Keywords: Late Cretaceous; soft-sediment deformation structures; intraplate tectonism; seismicity; overloading; Baum Basin